Effect of water-deficit on stem reserve mobilization for grain filling in wheat (Triticum aestivum L.) - Kaur, Kulveer; Ghai, Navita; Kaur, Satinder; Singh, Satinder; Sharma, Achla (Journal of Cereal Research, 2024)
The grain filling and development is considered as a key step for wheat yield and is most sensitive to water-deficit. In order to understand the effect of water-soluble carbohydrates (WSC) accumulation and mobilization on water-deficit tolerance, wheat lines viz., check PBW725, parent DS5Ut(5A) and introgression lines (ILs) (5U-24, 5U-26, 5U-27 and 5U-31) were used in this experiment. We examined the pattern of accumulation and mobilization water-soluble carbohydrates in peduncle (Ped), upper internodes (Uint), middle internodes (Mint) and basal internodes (Bint) under water-deficit. Bint showed highest mobilization WSC reserves for grain filling indicating that the lower portions of the stem may exhibit higher remobilization efficiency under water-deficit conditions. Among the ILs, IL 5U-26 showed highest mobilization of WSC in all the internodes. Correlation analysis depicted that increase in mobilization of WSC from Uint, Mint, Bint and Ped enhanced TGW significantly. Highest significant correlation of percent increase in TGW was found with percent change of WSC in Ped (0.97, significant at p